Monetary and exchange rate policy - Hodgman, Donald R.; Wood, Geoffrey Edward (Houndmills, Basingstoke, Hampshire : Macmillan Press in association with the Centre for Banking and International Finance the City University Business School, London, 1987)
The contributions in this volume are mainly concerned with exchange rate policy; decisions to alter fixed parities, intervention by central banks in foreign exchange markets, and the determinants of exchange rates including intervention and the degree of capital mobility. One examines policy reactions of the French monetary authorities, the other concerning the choice of monetary aggregate target as a politically motivated strategy.
Includes bibliographies and index.
aia 06/06/13; nmn 13/06/13
Loan
Keywords: Foreign exchange problem; Monetary policy